A Peace Tourism Model for Conflict Resolution between Religious Organizations in Indonesia - Fatkurrohman, Fatkurrohman; Makhasi, Ghifari Yuristiadhi Masyhari; Utsany, Royan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2024)
Indonesia, with its majority Muslim population, is home to two major Islamic organizations: Muhammadiyah and Nahdlatul Ulama (NU). Although both are rooted in the same faith, they often face tensions due to differing interpretations and religious practices. Most previous research has focused on their conflicts and rhetorical approaches to resolution, while practical strategies—such as tourism—have received little attention. This conceptual study explores how peace tourism can serve as a new way to foster reconciliation between Muhammadiyah and NU. Peace tourism refers to travel that facilitates dialogue and understanding between groups in conflict. This study introduces a simple, practical model of peace tourism that uses shared historical narratives and visits to significant sites of both organizations to bring the two groups closer and promote Ukhuwah Islamiyah (Islamic brotherhood). By participating in these joint trips, both groups can strengthen two key aspects of Islamic brotherhood: ta'aruf (getting to know one another) and tafahum (mutual understanding). The study draws on existing literature in conflict resolution and peace tourism, offering a theoretical exploration of how tourism can improve inter-group relations in Indonesia. It concludes with suggestions for tourism initiatives that could create space for meaningful dialogue and greater harmony between Muhammadiyah and NU.